The discipline of Western supremacy - Pijl, Kees van der (Pijl, Kees van der. Modes of foreign relations and political economy, 2014)
Concluding the acclaimed and award-winning trilogy on 'Modes of Foreign Relations and Political Economy', this is a magisterial historical sociology of International Relations theory. In The Discipline of Western Supremacy Kees van der Pijlargues that, from the late European Middle Ages, Anglophone thinkers articulated an imperial world-view which was adopted by aspirant elites elsewhere. Nation-state formation under the auspices of the English-speaking West has henceforth informed thinking about international affairs. After decolonisation the study of comparative politics continued to develop under those same auspices as part of a comprehensive framework. This book, the first of its kind, aims to provide a complete overview of mainstreamInternational Relations as a set of theories which translate Western supremacy into intellectual hegemony.